A comparative study on knowledge, attitudes, and practices of exclusive breastfeeding of lactating mothers attending a private and public hospital in Ibadan, Nigeria - Omotola, Yetunde Adebayo; Israel, Akinremi Tobi; Owolodun, Babatunde; Quadri, Jelili Akorede; Okoh, Ene (World Nutrition, 2025)
Background Breastfeeding is essential for infant health and survival. In 2023, only 29% of mothers of infants 0-6 months old in Nigeria exclusively breastfed their infants prior to the survey, despite a high percentage (95%) who initiated breastfeeding early. Various nutrition interventions have been implemented to improve mothers’ knowledge, attitudes, and practices (KAP) regarding exclusive breastfeeding. However, there is little data on exclusive breastfeeding KAP among mothers attending public and private hospitals in the Ibadan North Local Government Area, the focus of this study. Objective This study aimed to assess and compare the knowledge, attitudes, and practices of EBF among mothers attending outpatient clinics at a public and a private hospital in Ibadan North Local Government Area (LGAs). Methods A descriptive cross-sectional study conducted between February and March 2023 at Adeoyo Maternity Teaching Hospital (public) and Vine Branch Medical Centre (private) Ibadan. Total outpatient population sampling was used to recruit 160 lactating mothers (80 per hospital) at the immunization clinics. Information on mothers’ breastfeeding KAP was obtained using a semi-structured, interviewer-administered questionnaire. Knowledge was categorized as poor (0-7) or good (8-15); practice as poor (0-3) or good (4-7); and attitude as negative (0-8) or positive (9-17). Data were analysed using SPSS version 20.0. Descriptive and inferential statistics such as chi-square tests, Fischer’s Exact test, t-tests, and regression were used. Results Mean ages were 31.4±4.2 and 29.9±5.45 years at private and public hospitals, respectively. Most (91.2%) private hospital mothers had a tertiary education, unlike the public hospital (51.2%). We found good EBF knowledge among respondents in both hospitals (97.5%). A significant relationship was observed between hospital type and breastfeeding attitudes and practices. Poor breastfeeding practices were more prevalent at the private hospital (50.0%) than at the public hospital (30.0%). A statistically significant association was also found between Breastfeeding knowledge, marital status, occupation, breastfeeding attitude, and educational level. Conclusions High EBF knowledge was observed, but this did not consistently translate into attitudes or practices. Intervention should focus on approaches for converting knowledge into effective practice.